Abnormal development of placenta in HtrA1-deficient mice - Hasan,M.Z. (Academic Press Inc., 2015)
© 2014 Elsevier Inc. Abnormal levels of High temperature requirement A1 (HtrA1) protein have been repeatedly observed in sera and placentas of preeclampsia patients. To understand the functions of HtrA1 in placentation and in the etiology of preeclampsia, we established HtrA1-/- mice. HtrA1-/- mice show intrauterine growth retardation, and their placentas are small due to a reduced size of the junctional zone and aberrant vascularization in the labyrinth at the mid-gestation stage. HtrA1 is expressed by Tpbpa-positive trophoblast precursors in the outer ectoplacental cone and junctional zone from embryonic day 7.5 to 10.5. In the HtrA1-/- placenta, Tpbpa-positive cell precursors are decreased in the early stage. Spongiotrophoblasts and glycogen trophoblast cells, both of which differentiate from Tpbpa-positive precursors, are consequently decreased in the junctional zone. Fewer spiral artery-associated trophoblast giant cells, another cell type derived from Tpbpa-positive precursors, invade the decidua and associate with maternal arteries in the HtrA1-/- placenta than in the wild type placenta. Maternal arteries in the HtrA1-/- decidua have narrower lumens, thicker arterial walls, and more vascular smooth muscle cells remaining in the walls than those in the wild type decidua, indicating impaired remodeling of maternal arteries. These results indicate that HtrA1 plays important roles in the differentiation of trophoblasts from Tpbpa-positive precursors in the ectoplacental cone. Insufficient levels of HtrA1 cause poor placental development and intrauterine growth retardation, due to aberrant trophoblast differentiation and consequent defects in maternal artery remodeling, and may contribute to the onset of preeclampsia.